Busca por excesso no infravermelho médio em estrelas evoluídas com fotometria WISE e 2MASS - Silva, Danielly Freire da (2015)
Debris discs are commonly detected orbiting main-sequence stars, but little is known regarding their fate as stars evolve along subgiant and giant stages. Jones (2008) has found strong evidence on the presence of mid-IR excess in G and K stars of luminosity class III, using photometric data from the Two-Micron All-Sky Survey (2MASS) and GLIMPSE catalogues. While the origin of these excesses remains uncertain, it is plausible that they arise from debris discs around these stars. The present study brings an unprecedent survey in the search for mid-IR excess among single and binary F, G and K-type evolved stars of luminosity classes IV, III, II and Ib. For this study, we use WISE and 2MASS photometric data for a sample of 3000 evolved stars, complete up to visual magnitude of 6.5. As major results, we found that the frequency of evolved stars showing mid-IR WISE excess increases from the luminosity classes IV and III to luminosity classes II and Ib. In addition, there is no clear difference between the presence of IR excess in binary and single stars for all the analyzed luminosity classes.